Decellularized scaffolds and organogenesis: methods and protocols - Turksen, Kursad (Methods in molecular biology, 2018)
Decellularization Methods for Scaffold Fabrication -- Decellularized Liver Scaffold for Liver Regeneration -- Wharton's Jelly Matrix Decellularization for Tissue Engineering Applications -- 3D-Decellularized Native Extra Cellular Matrix Scaffold for In Vitro Culture Expansion of Human Wharton Jelly Mesenchymal Stem Cells (hWJ MSCs) -- Decellularized Iliotibial Band Recolonized with Allogenic Homotopic Fibroblasts or Bone Marrow-Derived Mesenchymal Stromal Cells -- Preparation of Cell-Derived Decellularized Matrices Mimicking Native ECM During the Osteogenesis and Adipogenesis of Mesenchymal Stem Cells -- Mouse Skeletal Muscle Decellularization -- Extracellular Matrix from Whole Porcine Heart Decellularization for Cardiac Tissue Engineering -- In-Lab Manufacturing of Decellularized Rat Renal Scaffold for Kidney Bioengineering -- Glutaraldehyde Crosslinking Modification of Decellularized Rat Kidney Scaffolds -- Preparation of Scaffolds from Decellularized Testicular Matrix -- Decellularization of Bovine Small Intestinal Submucosa -- Decellularization and Recellularization of Cartilage -- A Protocol to Prepare Decellularized Stem Cell Matrix for Rejuvenation of Cell Expansion and Cartilage Regeneration -- Tracheal Cartilage Isolation and Decellularization -- Protocols for Rat Uterus Isolation and Decellularization: Applications for Uterus Tissue Engineering and 3D Cell Culturing -- Application of Decellularized Tissue Scaffolds in Ovarian Tissue Transplantation -- Composite Bioscaffolds Incorporating Decellularized ECM as a Cell-Instructive Component within Hydrogels as In Vitro Models and Cell Delivery Systems -- 3D-Printing Composite Polycaprolactone-Decellularized Bone Matrix Scaffolds for Bone Tissue Engineering Applications -- Decellularization of Large Tendon Specimens: Combination of Manually Performed Freeze‑Thaw Cycles and Detergent Treatment -- Decellularized Bone Matrix Scaffold for Bone Regeneration -- Preparation of Decellularized Liver Scaffolds and Recellularized Liver Grafts -- Decellularization of Liver and Organogenesis in Rats -- Simple and Quick Method to Obtain a Decellularized, Functional Liver Bioscaffold -- Liver Bioengineering Using Decellularized Whole-Liver Scaffolds -- Decellularization of Intact Lung Tissue through Vasculature and Airways Using Negative and Positive Pressure -- Alveolar Rhabdomyosarcoma Decellularization.